Editorial: the increasing burden of microscopic colitis. Issue 2 (27th June 2019) - Guagnozzi, Danila; Tontini, Gian Eugenio; Pastorelli, Luca
Abstract : Linked Content This article is linked to Fernandez‐Bañares et al paper. To view this article, visit https://doi.org/10.1111/apt.13477 .